Cytometric analysis of adipose tissue reveals increments of adipocyte progenitor cells after weight loss induced by bariatric surgery. Issue 1 (December 2018) - García-Rubio, Jesús; León, Josefa; Redruello-Romero, Anaïs; Pavón, Esther; Cozar, Antonio; Tamayo, Francisco; Caba-Molina, Mercedes; Salmerón, Javier; Carazo, Ángel
Abstract Obesity-related comorbidities are, in large part, originated from the dysfunction of adipose tissue. Most of them revert after the normalization of body mass. Adipose tissue is essentially occupied by adipocytes. However, different populations of immunological cells and adipocyte precursor cells (AdPCs) are the main cellular components of tissue. During obesity, body fat depots acquire a low-level chronic inflammation and adipocytes increase in number and volume. Conversely, weight loss improves the inflammatory phenotype of adipose tissue immune cells and reduces the volume of adipocytes. Nevertheless, very little is known about the evolution of the human AdPCs reservoir. We have developed a flow cytometry-based methodology to simultaneously quantify the main cell populations of adipose tissue. Starting from this technical approach, we have studied human adipose tissue samples (visceral and subcutaneous) obtained at two different physiological situations: at morbid obesity and after bariatric surgery-induced weight loss. We report a considerable increase of the AdPCs reservoir after losing weight and several changes in the immune cells populations of adipose tissue (mast cells increase, neutrophils decrease and macrophages switch phenotype). No changes were observed for T-lymphocytes, which are discussed in the context of recent findings.